Erotiese oordrag en teenoordrag as psigologiese fenomeen in "n pastorale relasie - Dreyer, T. F. (HTS teologiese studies, 2004)
The psychological phenomenon of erotic transference and countertransference within the framework of pastoral careThis article aims to discuss the psychological phenomenon of transference and countertransference in therapeutical relationships. This phenomenon often leads to a sexual relationship resulting in emotional and psychological damage to both partners. The cause of this destructive sexual relationship is based on the therapist’s misunderstanding of positive transference within the therapeutic relationship. The therapist, unknowingly in most instances, misuses his or her position of trust for sexual exploitation of the client. This phenomenon also manifests in pastoral relationships. This article describes the phenomenon and provides possible guidelines to the pastor in order to identify and prevent the occurrence of “sex in the forbidden zone.”